Scourge the once and future threat of smallpox - Tucker, Jonathan B. (Atlantic Monthly Press, 2001)
This book provides a definitive account of the dramatic story of smallpox by a leading expert on biological and chemical weapons. The author traces the history of the smallpox virus from its first recorded outbreak around 3700 B.C. through its use as the first biological warfare agent in human history, and draws some decisively important lessons for the future. In a timely debate, he addresses the ever-growing concerns about the proliferation of the deadly smallpox virus and its use by terrorist organizations. Explaining how the eradication of the disease in the late 1970s encouraged military research and production of the virus, he exposes the failure of the Russian government to secure its remaining cold-war stockpiles, and evaluates the past and present measures undertaken by the United States to counter the existing dangers of a smallpox attack. Ultimately, he passionately argues for the strengthening of the existing legal ban on the development and possession of biological weapons.
Keywords: Geschichte; Smallpox -- History; Smallpox -- history; Pocken; Kinderlähmung; Pockenviren; Biologische Waffe